Distribuição Espacial das Inundações em Goiânia (GO) e Análise desse Fenômeno na Bacia do Córrego Pedreira - SANTOS, Késia Rodrigues dos (2010)
The present work was realize in two scale, the first of spacious character of consider the inundations happened in Goiânia city, and in the second phase detail the hydrographic basin of Pedreira stream localized in north-east region of Goiânia, in the Goiás state. The objective of this work was spatialization the area of inundation risk in Goiânia and identify the cause and consequence of inundations of Pedreira stream. The choose of area in the study of agenda in resort to accidents register in the basin and the number of people victim these events, that it is significant in relation all areas risk in the capital. It searched analyze the naturals and the occupation of area characters through survey of fact, search of bibliography, Fieldwork, mapping of morphologic and morphometric characters in this basin, mapping land use, interviews with residents, separation of inundations area / accident and elaboration of susceptibility map. For the mapping we adopted the scale 1/20.000. The results took a conclusion that the inundations happen because the condition of physical process that was intensify for basin occupation. The naturals conditions, related of physical process, include the regime of rain of the region, the high slope in the portion more higher of the basin, like relief rugosity, the variation hypsometric, tendency to the concentration of the flow in some concave segments, the form the hydrographic basin and the existence of inundation plain in half basin, the siltation and strangle of the drainage. The basin of Pedreira stream happen than occupation of irregulars dwelling of areas destined to preservation, in the inundation plain in the bank Pedreira stream. The population, include children, is subject at the inundation occurrence.